Inventory of Diderot's Encyclopédie: plates - Schwab, R; Rex, W (Voltaire Foundation, 2017)
Introduction General considerations Essay on the relation of the plates, articles, and explications Problems of attribution, particularly regarding Diderot The plates and the problem of attribution of the unsigned articles The physical production of the plates: the craftsmen and artists Inventory of the plates Part I: Description of the plates The original edition, Census of the plates Collation of volumes I-XI The supplementary volume of plates (XII), and Collation The plates of the ‘Geneva’ edition, Collation and Main check points for identification Part II: Comprehensive inventory of the plates Volumes I-XI and Volume XII (Supplément) Part III: Index of articles containing references to the plates Volumes I-XVII and Supplément Volumes I-IV Part IV: Index of objects depicted in the plates Part V: Index of contributors to the plates Errata and addenda for volumes I-VI of the Inventory General table of contents for volumes I-VI J. LOUGH, The Contributors to the Encyclopédie Introduction 1. The contributors to the Encyclopédie 2. The contributors to the Supplément 3. Notes on the contributors to the Encyclopédie 4. Notes on the contributors to the Supplément Index